RAG mutations in human B cell-negative SCID - Schwarz, Klaus; Gauss, George H.; Ludwig, Leopold; Pannicke, Ulrich; Li, Zhong; Lindner, Doris; Friedrich, Wilhelm; Seger, Reinhard A.; Hansen-Hagge, Thomas E.; Desiderio, Stephen; Lieber, Michael R.; Bartram, Claus R. (Science, 1996)
Patients with human severe combined immunodeficiency (SCID) can be divided into those with B lymphocytes (B+ SCID) and those without (B− SCID). Although several genetic causes are known for B+ SCID, the etiology of B− SCID has not been defined. Six of 14 B− SCID patients tested were found to carry a mutation of the recombinase activating gene 1 (RAG-1), RAG-2, or both. This mutation resulted in a functional inability to form antigen receptors through genetic recombination and links a defect in one of the site-specific recombination systems to a human disease.